The influence of mobile service quality on customer loyalty of Gojek with customer satisfaction as a mediated variable - Guntur, Muhammad Fauzan Samudera Putra; Martini, Erni (Edelweiss Applied Science and Technology, 2025)
The phenomenon discussed in this research focuses on the importance of service quality provided through mobile applications in creating a strong relationship between customers and the company. Customer satisfaction becomes a key factor that mediates the influence of service quality on customer loyalty. This research investigates how good mobile service quality can enhance customer satisfaction, which in turn contributes to increased loyalty among Gojek users. This research employs a quantitative approach, with non-probability sampling, data collected through online questionnaires via Google Forms, and involves 385 respondents who are active users of Gojek services in Indonesia. The analysis was conducted using Structural Equation Modeling (SEM) with AMOS software to test the relationships between variables and assess the fit of the research model with the obtained data. The results of this research are expected to provide insights for Gojek in improving service quality to strengthen customer loyalty amid the increasingly competitive digital service industry.